Where Schumpeter was Nearly Right - The Swedish Model and Capitalism, Socialism and Democracy - Magnus Henrekson; Ulf Jakobsson (The Research Institute of Industrial Economics (IUI), 2000)
In Capitalism, Socialism and Democracy Joseph A. Schumpeter concluded that socialism would eventually displace capitalism in Western democracies. This would come about as a result of the superior performance of capitalism. We extract six 'stylized' propositions that are essential elements of Schumpeter's prediction about the fate of capitalism. These propositions are confronted with the development of the Swedish economy. The three main results of the analysis are: (1) The evolution of the Swedish economy closely followed Shumpeter's predictions until about 1980: Large firms became increasingly predominant in production and innovative activity, ownership of firms became more and more concentrated, individual entrepreneurship waned in importance, the general public grew increasingly hostile towards capitalism, and by the late 1970s explicit proposals for a gradual transfer of ownership of firms from private hands were launched. (2) Design of tax and industrial policies fueled a development of the economy along the lines predicted by Schumpeter. In general, the policies discouraged private wealth accumulation. In particular, the policies favored concentration of firms and concentration of private ownership. (3) The turning point away from the path to socialism coincides with real world developments that disclosed two major flaws in Schumpeters analysis. First, the ever more obvious failure of socialism in Eastern Europe went against Schumpeter's assertion that socialism can work. Second, Schumpeter, who thought that modern technology would make the giant corporation increasingly predominant, did not foresee the revival of entrepreneurship that took place in the Western countries around 1980.
Keywords: M13; O38; P16; 330; Corporatism; Entrepreneurship; Industrial Policy; Schumpeter; Swedish Model; Volkswirtschaft; Kapitalismus; Sozialismus; Sozialstaat; Schweden